Risk of Urticaria in Children with Type 1 Diabetes Mellitus: A Nationwide Cohort Study - Lin, Shih-Yi (Int J Environ Res Public Health, 2019)
Type 1 diabetes mellitus (T1DM) has been linked to many autoimmune problems. The association between T1DM and urticaria warrants investigation. Data were extracted from the National Health Insurance Research Database (NHIRD) of Taiwan. Participants with T1DM were recruited as the case group, and that group was matched by sex and age at a ratio of 1:4 to the control group comprising those without T1DM. The study period was 1998–2011. All participants were followed up to the diagnosis of urticaria, withdrawal from the insurance program, death, or the end of the study. A multivariable Cox proportional hazard model was used to calculate the adjusted and crude hazard ratios for urticaria. A total of 5895 participants (1179 in the case group and 4716 in the control group) were followed up in the study. The total incidence rate of urticaria in patients with type 1 DM was 26.6 per 1000 person-years, and that in controls was 6.85 per 1000 person-years. Compared with the control group, the hazard ratio of urticaria in the case group was 2.84 (95% CI = 2.27–3.56). Compared with age-matched participants without T1DM, patients with type 1 DM aged <18 years had a 3.62-fold higher risk of urticaria (95% CI = 2.85–4.59). The hazard ratio in patients with an adjusted Diabetes Complications Severity Index (aDCSI) score of 1.01–2.00 per year was 2.57 (95% CI = 1.18–5.57), and that in patients with an aDCSI score of >2.00 per year was 4.47 (95% CI = 2.68–7.47). T1DM patients aged <18 years had an increased risk of urticaria, but a similar phenomenon was not observed among T1DM patients older than 18 years.